PENGARUH KUALITAS PELAYANAN DAN PERIKLANAN TERHADAP KEPUTUSAN NASABAH DALAM MENABUNG PADA PT. BPR KABUPATEN SERANG - Regiasa, Tubagus (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2023)
This research aims to analyze the influence of service quality and promotion together on customers' decisions to save at PT. BPR Serang Regency. The population in this study is the total number of customers who save at PT BPR Serang Regency during 2022, amounting to 300 respondents. Meanwhile, the sample was 75 respondents. The sampling technique in this research used Accidental Sampling. The analytical tool used in this research is multiple linear regression analysis, where previously validity and reliability tests and classical assumption tests were carried out. Based on the results of the research above, it can be concluded that the quality of service should be improved, especially regarding the management of human resources for optimum performance, for example holding employee training and development, company management should present advertisements that attract more attention, such as the frequency of advertisements being broadcast, so that people are interested. and want to become customers, in an effort to increase customers' decisions to save, employees should frequently make contact with customers, such as notifications of increases in bank interest rates, so that this will remind customers to keep saving.